Agreement between anterior segment parameters obtained by a new ultrasound biomicroscopy and a swept-source fourier-domain anterior segment optical coherence tomography. (1st December 2020) - Li, Xiuyuan; Chang, Pingjun; Li, Zhangliang; Qian, Shuyi; Zhu, Zehui; Wang, Qianwei; Yun-E, Zhao
ABSTRACT: Purpose : To evaluate the agreement between anew UBM and an SS-OCT. Methods : The scans of the right eye of each volunteer were obtained using the two devices. Data were fitted and recorded including: central corneal thickness (CCT), aqueous depth (AQD) (the distance from endothelium to lens), angle-to-angle distance (ATA), lens thickness (LT), diameter of the lens in the horizontal direction (LDia angle : distance between the sharp angles on both sides of the lens, LDia arc : distance between the vertex of the circular arcs on both sides of the lens), anterior and posterior corneal radius (Rf and Rb). Results : 25 eyes were included in this study. It could be seen that the differences in CCT, LDia angle, Rf measured by the two instruments were not statistically significant. Bland-Altman analysis plots of CCT, LDia angle and Rf showed mean differences of 0.2 µm, 0.01mm and 0.0mm for the 2 devices, respectively. Conclusion : The values of CCT, LDia angle and Rf obtained via two instruments were not clinically interchangeable and the AQD, ATA, LT, and Rb have poor agreement affected by accommodation. We can estimate the real lens diameter by subtracting 0.61 ± 0.43mm when the lens diameter can only be simulated with SS-OCT.